1989
DOI: 10.1021/bi00432a010
|View full text |Cite
|
Sign up to set email alerts
|

Solution structure of an analog of vasoactive intestinal peptide as determined by two-dimensional NMR and circular dichroism spectroscopies and constrained molecular dynamics

Abstract: Structures have been determined for a potent analogue of vasoactive intestinal peptide (VIP), Ac-[Lys12, Lys14, Nle17, Val26, Thr28]VIP (VIP'), in methanol/water solutions. In CD studies, both VIP and VIP' were helical in methanol/water, with the percentage of alpha-helix increasing with percentage methanol. The pH had little effect on the structure. Complete 1H NMR assignments were made for VIP' in 25% methanol at pH 4 and 6 and in 50% methanol at pH 6, using two-dimensional COSY, NOESY, and relay-COSY experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
46
0

Year Published

1991
1991
2005
2005

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 59 publications
6
46
0
Order By: Relevance
“…3). This is in good agreement with previous experimental studies of the VIP structure in methanol/water solutions using nuclear magnetic resonance and circular dichroism which also indicated that the structure of VIP is mostly helical (48) with the existence of a central well defined ␣-helix, the remaining residues being not ordered (49). Similarly, PACAP38 was shown to have a disordered N-terminal domain followed by a central ␣-helical structure (50).…”
Section: Discussionsupporting
confidence: 91%
“…3). This is in good agreement with previous experimental studies of the VIP structure in methanol/water solutions using nuclear magnetic resonance and circular dichroism which also indicated that the structure of VIP is mostly helical (48) with the existence of a central well defined ␣-helix, the remaining residues being not ordered (49). Similarly, PACAP38 was shown to have a disordered N-terminal domain followed by a central ␣-helical structure (50).…”
Section: Discussionsupporting
confidence: 91%
“…The dramatic loss of VPAC1 and VPAC2 activation caused by proline replacement at position 19 of R3P65 is consistent with the importance of maintaining the helical structure for its function since proline has been characterized as a "helix breaker" (30). On the other hand, proline did not significantly affect VPAC2 selectivity and potency at positions 27, 29, and 30 presumably because these residues fall outside of the predicted helical region (23)(24)(25)(26). Most of the mutant peptides from saturation mutagenesis at positions 29 and 30 possessed at least 3-fold greater VPAC2 selectivity than R3P49 (V19A/L27K-VIP), which differs from R3P65 in not having the two amino acid extension.…”
Section: Figsupporting
confidence: 63%
“…Both peptides possess a low percentage of stable structure in aqueous solution but an increasing percentage of helicity as the ratio of organic co-solvent is increased (23)(24)(25)(26). At ϳ50% organic solvent, residues 8 -26 generally adopt a helical structure while the N and C termini remain highly flexible with little discernible structure.…”
Section: Discussionmentioning
confidence: 99%
“…The integrity of the helices is important for high affinity binding (33). A similar structural arrangement is also detected in VIP (36). The first 6 amino-terminal residues of PACAP are important for both binding and signal transduction.…”
Section: Discussionsupporting
confidence: 63%